The Digital Paradox in Schools: Navigating The Intersection between Artificial Intelligence and Academic Performance - Friyanda, Nurul Fahri; Dartim, Dartim (Universitas Muhammadiyah Surakarta, 2025)
The acceleration of the digitalization of education and the introduction of artificial intelligence (AI) into the classroom have created a